The Effectiveness of Health Education about Healthy Pregnancy through WhatsApp Group towards the Knowledge of Pregnant Women at Bakunase Health Center Kupang City 2019 - Yuliana Dafroyati; Ririn Widyastuti (Alliance oh Health Activists (AloHA), 2020)
One thing we can do to enrich pregnant women knowledge is through health education about healthy pregnancy. Digital era, known as Web 2.0, or Health 2.0, or Medicine 2.0, makes healthy people and patients rely more on the internet than doctors or health workers as a source of health care information. The number of internet users in Indonesia is growing, reaching up to 64.6% or 171 million citizens. WhatsApp is the most popular application for people to communicate via internet. Thus, it needs to be analyzed the opportunities giving knowledge about health education and health promotion through WhatsApp. The purpose of this study was to determine the effectiveness of health education about healthy pregnancy through WhatsApp group towards the knowledge of pregnant women at Bakunase Health Center, Kupang City. Researchers used experimental research. They used quasi experimental research design with pretest and posttest design. The population in this study were 95 pregnant women in the work area of Bakunase Health Center in 2019. The sampling technique used was purposive sampling, with sample were 48 people. The results of paired samples t-test show that there was a difference between the average pre and post intervention in the provision of health education about healthy pregnancy through WhatsApp group for pregnant women with a p value of 0.0001. The intervention of providing health education about healthy pregnancy towards pregnant women at Bakunase Health Center in Kupang City through WhatsApp group was effective in increasing the knowledge of pregnant women about healthy pregnancy. Keywords: health education; WhatsApps group; knowledge; pregnant women